Interrater reliability of the Eating Disorder Examination among post-bariatric patients - Wiedemann, Ashley A. (Surg Obes Relat Dis, 2020)
BACKGROUND: Clinical assessment of eating behaviors with patients who undergo bariatric surgery is challenging due to the complexity of symptom presentation post-operatively. The Eating Disorder Examination (EDE) is a widely-used semi-structured clinical interview of eating-disorder psychopathology, yet no studies have examined the interrater reliability among postoperative bariatric surgery patients. OBJECTIVES: The present study aimed to examine the interrater reliability of the EDE, and an alternative classification of size-specific thresholds of binge-eating episodes in a postoperative bariatric surgery sample. SETTING: University School of Medicine, United States METHODS: Participants interviewed were a randomly selected subset (N=20) from a consecutive series of adults seeking treatment for eating concerns following bariatric surgery. Audio-taped interviews were rated independently by one of four expert raters. Interrater reliability was assessed using intra-class correlation coefficients (ICC) and kappa statistic. RESULTS: ICCs for the original four EDE subscales were excellent, ranging from 0.88 to 0.98. ICCs for the alternative brief three subscales were also excellent, with a range of 0.78 to 0.97. ICCs for bariatric-LOC eating episodes were in the good to excellent range, with a range of 0.66 to 0.99. Kappa agreement for bariatric overeating episodes was moderate (0.60). CONCLUSIONS: These findings, based on four expert raters, suggest that complex eating-disorder psychopathology, as well as the newly-proposed eating behavior with size thresholds relevant to bariatric patients, can be reliably assessed. This is the first study to provide initial evaluation and support for the interrater reliability of the original EDE with additional modified eating categories developed for post-bariatric surgery patients.